Análise de herança da resistência à ferrugem da cana-de-açúcar P. melanocephala H. & P. Syd - Moura, Guilherme Lacava de (2004)
Sugarcane rust (Puccinia melanocephala) is a major disease distributed throught the world, causing yield losses of 50% in conducive environments. Resistance is an essential trait to control rust in commercial cultivars requiring routine tests along the selection time in breeding programs. In order to better understand the complexity and to determine the inheritance of rust resistance in brazilian sugarcane cultivars, this work analyzed eight F1 segregating populations involving 10 genotypes as parents. The resistance was polygenic where the segregation of several minor genes in each progeny was responsible for their classification in the different resistance levels from 2 to 9. Besides polygenetic resistance, the presence of major genes segregating 1:1 and 3:1 deviated the individuals to the grade 1, corresponding to complete resistance. It was observed transgressive segregation, generating resistance genotypes from susceptible-susceptible crosses. Therefore, to achieve resistant cultivars it not necessary to chose resistant parent if effective tests are used to screen susceptible genotypes during selection. It was also observed maternal effects in segregation, deviating individuals to rust resistance.